A Review of Veterinary and Economically Devastating Coronaviruses: Emphasising Poultry and Pigs - ISMAIL, Mohd Iswadi (BioScientific Review, 2023)
Coronaviruses are known can cause a significant impact on veterinary medicine and socio-economic. Understanding the biological characteristics and dynamics of pathogenic coronaviruses is a major scientific challenge with potential impacts on animal health. Coronaviruses are typically known to cause respiratory or enteric diseases in poultry and pigs. However, some coronavirus strains may cause extra-pulmonary and extra-intestinal disorders. Keeping in view the limitations of the current knowledge, the impact of coronaviruses on poultry and pigs was examined.